The Impact of Economic Growth and Foreign Investment on the Advancement of E-commerce - Du Wenyang; Yihong Zhang; Bolot Dzhamankulov (Qubahan Academic Journal)
This study examines the interrelationship between economic growth, foreign investment, and e-commerce development in Kyrgyzstan from 2010 to 2022. Using correlation and regression analyses, the research reveals a strong positive relationship between foreign investment and GDP growth, with a 1% change in foreign investment corresponding to a 0.86% change in GDP. The study finds that increased investment and economic growth in key sectors such as information and communication, financial intermediation, and trade have significantly contributed to e-commerce expansion. This is evidenced by increases in Internet access points, mobile subscriptions, and bank card circulation. The research utilizes the UNCTAD B2C E-commerce Index to track Kyrgyzstan's progress in e-commerce readiness, showing improvements correlating with economic and investment growth. Practical implications for policymakers were created. It is recommended to prioritize policies that attract foreign investment, particularly in ICT, financial services, and trade sectors to stimulate e-commerce growth; develop targeted strategies to improve digital infrastructure and increase internet accessibility nationwide; implement regulations that facilitate secure online transactions and protect consumer rights in e-commerce; invest in digital literacy programs to increase e-commerce adoption among the population; create incentives for businesses to develop online platforms and integrate e-commerce into their operations; foster partnerships between foreign investors and local businesses to transfer knowledge and technology in e-commerce.